Functional innovation promotes diversification of form in the evolution of an ultrafast trap-jaw mechanism in ants - Booher, Douglas B.; Gibson, Joshua C.; Liu, Cong; Longino, John T.; Fisher, Brian L.; Janda, Milan; Narula, Nitish; Toulkeridou, Evropi; Mikheyev, Alexander S.; Suarez, Andrew V.; Economo, Evan P. (PLOS Biology, 2021)
The mousetrap-like mandibles of trap-jaw ants are a functional innovation capable of record-breaking acceleration. This study uses phylogenomics, X-ray microtomography and high-speed videography to reveal that they evolved multiple times around the world through a pathway of incremental steps.